Maintenance planning and scheduling handbook - Palmer, Doc (McGraw-Hill, 1999)
Helps facilities managers to improve the productivity of their maintenance plan. This guide identifies the six basic principles of planning and the six associated principles of scheduling. It provides how-to information on implementing a planning function, using work orders, and performing in-house work sampling.